Mediated learning and the brain - Wilson, Donna; Fifth International Teaching for Intelligence Conference (Arlington Heights, IL : SkyLight Professional Development, 1999)
Wilson explores the theory of mediated learning and how it impacts students' abilities to improve thinking skills
Executive producer, Ela Aktay
Keywords: Thought and thinking -- Study and teaching; Learning, Psychology of; Cognition in children